2011
DOI: 10.1016/j.bbmt.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan Testing in Bronchoalveolar Lavage Fluid Facilitates the Diagnosis of Invasive Pulmonary Aspergillosis in Patients with Hematologic Malignancies and Stem Cell Transplant Recipients

Abstract: Invasive pulmonary aspergillosis (IPA) is a major cause of mortality in patients with stem cell transplants and hematologic malignancies. Timely diagnosis of IPA improves survival but is difficult to make. We evaluated the effectiveness of bronchoalveolar lavage (BAL) galactomannan (GM) in diagnosing IPA in these populations by retrospectively reviewing records of 67 consecutive patients, in whom 89 BAL GM tests were performed. For patients with IPA, only the first BAL sample linked to the IPA episode was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 38 publications
5
58
0
Order By: Relevance
“…Hence, for daily clinical practice, a lower OD index cutoff value (0.8) seems to be much more appropriate, as evidenced by the ROC analysis. This lower cutoff is also in line with previously published experiences (24). Of note, at these lower values, the pretest probability of disease remains crucially important for determining the posttest probability (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hence, for daily clinical practice, a lower OD index cutoff value (0.8) seems to be much more appropriate, as evidenced by the ROC analysis. This lower cutoff is also in line with previously published experiences (24). Of note, at these lower values, the pretest probability of disease remains crucially important for determining the posttest probability (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Hence, a culture-independent method may increase the yield of BAL fluid samples. Recently, the clinical utility of GM EIA detection using BAL fluid samples has been explored in a variety of adult and pediatric populations; these studies, which use various OD cutoff indices for positivity, have reported high sensitivities in hematology patients (2,3,7,13,19,22,24,26,28,30), most solid-organ transplant recipients (4), critically ill patients (21), and nonimmunocompromised patients (23). However, significantly lower sensitivities have been reported in lung transplant recipients (4,15,18,27).…”
Section: Discussionmentioning
confidence: 99%
“…due to the use of mold-active antifungal prophylaxis and corticosteroids) are possible [Marr et al 2005[Marr et al , 2004Mennink-Kersten et al 2004]. Furthermore, GM assay in BAL specimen has shown promising results and adds to the sensitivity of the serum GM assay [Nguyen et al 2010;Meersseman et al 2008].…”
Section: Serologic Evidencementioning
confidence: 99%
“…Bronchoalveolar lavage galactomannan was positive in all patients who had invasive fungal infection and were on active antifungal therapy for < 3 days. 53 Serum galactomannan can be falsely elevated in patients with gastrointestinal GVHD and those receiving beta lactams such as piperacillintazobactam. 54 Elevated serum 1,3-beta-D-glucan assay levels may be useful in the diagnosis but is not well defined in patients with IPA.…”
Section: Invasive Fungal Infectionsmentioning
confidence: 99%